Anterolateral Bone Window for Revision Broken Cemented Stem of Unipolar Hemiarthroplasty - Mohamed Mosa Mohamed Mahmoud; Bahaaeldin Ibrahim; Amr Abdelhalem Amr; Maysara Abdelhalem Bayoumy (Advances in Orthopedics)
Background. Fractured stem of the hip prosthesis is well documented in the literature. Although it is rare, it is considered as a challenging problem. Many techniques have been described to solve this problem. Purpose of the Study. Evaluation of the effect of anterolateral bone window for extraction of the cemented femoral stem of hemiarthroplasty in revision total hip replacement. Methods. The study included eight revision hip arthroplasties in eight patients, with a broken stem of cemented (Thompson) hemiarthroplasty, which has been revised by the anterolateral proximal femoral window. All cases received cemented cups and cement-in-cement stems, except one case who received cementless long stem. Clinical follow-up of cases by Harries hip score (HHS) and X-ray. Results. Functional improvement of HHS of all cases, with no signs of loosening, after a mean follow-up period of 1.5 years. Conclusion. Extraction of broken stem is a challenging procedure. Many techniques have been described for revision of cases with a fractured stem of hip prosthesis, but we think that the anterolateral femoral bone window is a reproducible technique due to the characteristics of simplicity, short-time procedure, less invasive, not requiring extra instruments, and can be successful for most patients.